Molecular mechanism of HNF-1A-mediated HNF4A gene regulation and promoter-driven HNF4A-MODY diabetes - Kind, Laura; Molnes, Janne; Tjora, Erling; Raasakka, Arne; Myllykoski, Matti; Colclough, Kevin; Saint-Martin, Cécile; Adelfalk, Caroline; Dusatkova, Petra; Pruhova, Stepanka; Valtonen-André, Camilla; Bellanné-Chantelot, Christine; et al. (JCI insight, 2024)
Monogenic diabetes is a gateway to precision medicine through molecular mechanistic insight. Hepatocyte nuclear factor 1A (HNF-1A) and HNF-4A are transcription factors that engage in crossregulatory gene transcription networks to maintain glucose-stimulated insulin secretion in pancreatic β cells. Variants in the HNF1A and HNF4A genes are associated with maturity-onset diabetes of the young (MODY). Here, we explored 4 variants in the P2-HNF4A promoter region: 3 in the HNF-1A binding site and 1 close to the site, which were identified in 63 individuals from 21 families of different MODY disease registries across Europe. Our goal was to study the disease causality for these variants and to investigate diabetes mechanisms on the molecular level. We solved a crystal structure of HNF-1A bound to the P2-HNF4A promoter and established a set of techniques to probe HNF-1A binding and transcriptional activity toward different promoter variants. We used isothermal titration calorimetry, biolayer interferometry, x-ray crystallography, and transactivation assays, which revealed changes in HNF-1A binding or transcriptional activities for all 4 P2-HNF4A variants. Our results suggest distinct disease mechanisms of the promoter variants, which can be correlated with clinical phenotype, such as age of diagnosis of diabetes, and be important tools for clinical utility in precision medicine.
Keywords: vazba proteinů; mužské pohlaví; Male; krystalografie rentgenová; Protein Binding; Crystallography, X-Ray; Humans; Female; regulace genové exprese; Hepatocyte Nuclear Factor 4; lidé; hepatocytární jaderný faktor 4; ženské pohlaví; promotorové oblasti (genetika); Diabetes Mellitus, Type 2; vazebná místa; Promoter Regions, Genetic; Binding Sites; diabetes mellitus 2. typu; hepatocytární jaderný faktor 1-alfa; Gene Expression Regulation; Hepatocyte Nuclear Factor 1-alpha